El acto administrativo como expresión de la función administrativa (2016)
The teacher Jaime Orlando Santofimio Gamboa makes clear that the democracy is the point of item and formal and substantial determinant of the totality of the activity and administrative function of the State and, therefore, it is consolidated as the modal of the juridical applicable regime for the exercise of happiness function, of which some beginning can be glimpsed as that of legality, prevalencia of the general interest, responsibility, prevalencia and respect of the fundamental rights, division of power and control of the public activity. (Santofimio, 1998) The contentious administrative jurisdiction, originated in the year of 1799 with the creation of the French State council, across his failures has created the doctrine of the modern administrative law.